2019
DOI: 10.1186/s12913-019-4326-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementing cancer prevention clinical decision support in primary care: a qualitative study

Abstract: Background In the United States, primary care providers (PCPs) routinely balance acute, chronic, and preventive patient care delivery, including cancer prevention and screening, in time-limited visits. Clinical decision support (CDS) may help PCPs prioritize cancer prevention and screening with other patient needs. In a three-arm, pragmatic, clinic-randomized control trial, we are studying cancer prevention CDS in a large, upper Midwestern healthcare system. The web-based, electronic health record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 19 publications
1
66
0
1
Order By: Relevance
“…Few studies have assessed PCPs’ attitudes about cancer screening and prevention in predominately rural areas. As noted elsewhere, engaging patients through cancer SDM with PCPs is challenging, particularly given current time constraints in primary care [23, 24]. Although 37% of PCPs were not very prepared to discuss cancer risk factors and screening with patients, less than half (49%) said that the EMR was well integrated to help assess and manage cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have assessed PCPs’ attitudes about cancer screening and prevention in predominately rural areas. As noted elsewhere, engaging patients through cancer SDM with PCPs is challenging, particularly given current time constraints in primary care [23, 24]. Although 37% of PCPs were not very prepared to discuss cancer risk factors and screening with patients, less than half (49%) said that the EMR was well integrated to help assess and manage cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Only 53% of respondents said that their patients give cancer screening a high priority in relation to other health services, and this percentage was even lower in advanced care practitioners. This finding could be due to several issues we identified in key informant interviews [24] and through continued engagement with our intervention clinics: lack of time for patients and/or providers to discuss cancer prevention; and patients visiting for acute reasons. Most PCPs also reported that they often do not have enough time to discuss screening or HPV vaccination with patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary Care Physicians (PCPs) play an increasing role in cancer risk assessment and prescribing of preventive interventions (25). Patients rely on their PCPs to identify their cancer risk and provide recommendations for risk reduction (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…We also have an incomplete understanding of whether shared decision making between patients and PCPs leads to improved cancer preventive care. Shared decision making involves PCPs presenting patients with cancer prevention and screening options, risk, and benefits, including when using decision aids, then assisting patients with making a decision that fits patients’ personal preferences [ 19 , 20 ]. Research shows that shared decision making between patients and PCPs is effective in the decision making process [ 18 ].…”
Section: Introductionmentioning
confidence: 99%